(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Perfluorine-organic compounds (PFOC) possess valuable qualities for vitreoretinal surgeries, and their use for short-term tamponade could expand indications to operative treatment and improve results. However, there is no unequivocal opinion concerning mechanical action of PFOC on the ultrastructure of the retina. Purpose. To study the influence of 7-day tamponade with PFOC on the ultra-structure of the eye retina of the rabbit in experiment; comparison of the effect of PFOC, a physiological solution and « light» silicone oil with viscosity of5700 cCm in dynamics by carrying out electron-microscopic study (EMS) on different terms after end tamponade Material and methods. The experimental research has been carried out on 12 rabbits (24 eyes). All animals were performed posterior closed subtotal vitrectomy with the subsequent 7-day tamponade with PFOC (the right eye), «light» silicone and physiological solution (the left eye). EMS was made after the end of tamponade in 7, 14 and 30 days. Results. Ultrastructural changes caused in the retinal elements revealed both under the influence of PFOC and silicone, are similar to each other. In reply to seven-day tamponade of the vitreal cavities with the applied substances, the structure of the retina react the same, mainly by hydroptic changes of elements of the smooth endoplasmatic network and mitochondria. Conclusion. After seven-day tamponade with the applied substances, structures of the retina react with the same changes. However, these changes are related to the category of reactive but not damaging and have reversible character. PFOC can be considered as candidates for carrying out short-term tamponade.